Deviation from the balanced time perspective and depression and anxiety symptoms: the mediating roles of cognitive-behavioral emotion regulation in a cross-cultural model - Abdollahpour Ranjbar, Hamed; Altan-Atalay, Ayse; Habibi Asgarabad, Mojtaba; Turan, Bulent; Eskin, Mehmet (Frontiers in Psychiatry, 2025)
BackgroundTime perspective (TP) influences how individuals perceive and classify their past, present, and future, impacting their cognition, behavior, and psychological outcomes. Deviation from the balanced time perspective (DBTP) is associated with mental health problems (e.g., depression and anxiety). Emotion regulation (ER) encompasses cognitive and behavioral processes to regulate emotions, with maladaptive strategies like rumination and withdrawal linked to depression and anxiety. Despite extensive research on TP and ER, their joint impact, particularly in the context of depression and anxiety, and cultural differences remain underexplored.MethodParticipants (N = 513 Iranian, N = 470 Turkish) completed self-report questionnaires on time perspective, cognitive and behavioral ER, anxiety, and depression symptoms. A moderated mediation model was assessed, incorporating the exogenous variable of DBTP, with ER strategies as mediators, and endogenous variables of depressive and anxiety symptoms. The model accounted for cultural variations in the paths as a moderator.ResultsSignificant associations were found between DBTP, ER strategies, depression, and anxiety symptoms. Mediation analyses revealed that both cognitive and behavioral ER strategies (except for adaptive behavioral ER strategies) significantly mediated the associations between DBTP and depression and anxiety. Additionally, multigroup analyses suggested that these mediating effects were consistent across Iranian and Turkish samples, with exceptions in adaptive cognitive ER strategies.ConclusionThe study highlights the crucial role of TPs and ER strategies in predicting anxiety and depression symptoms, with notable cultural nuances. Specifically, maladaptive strategies exacerbate symptoms, while adaptive strategies mitigate them primarily in Iranian contexts. Cultural subtleties are discussed in detail.